LOCAL ANTIBODY AND CELLULAR IMMUNE RESPONSES TO INFLUENZA INFECTION AND VACCINATION - G. D. Petukhova; A. N. Naikhin; I. B. Barantseva; S. A. Donina; T. V. Chirkova; E. P. Grigorieva; L. G. Rudenko (Медицинская иммунология)
Abstract. Local immune responses of mucous membranes of an organism are the first and most significant barriers preventing many virus infections, including influenza. The barrier against influenza infection is the mucosalassociated lymphoid tissue of the upper airways. It is considered, that nasopharyngeal-associated lymphoid tissue (NALT) in rodents is an equivalent of lymphoid tissue in human Waldeyer’s ring. Present work is the first attempt to analyze and compare the development of cellular and antibody immune responses in NALT in a mouse model of experimental influenza infection using a pathogenic influenza A (H1N1) virus and an attenuated reassorted (2/6 genetic formula) live influenza A (H1N1) vaccine.It was shown, that the vaccine strain inherits the ability to induce high-grade local antibody responses like as the virulent parental strain. However, the vaccine strain is inferior to virulent parental strain in capacity to stimulate production of circulating antibodies. Both parental and Р 2/6 strains are equally able to induce lymphoproliferative immune response in NALT lymphocytes. The attenuated reassortant virus is able to stimulate proliferation of Th (CD4+), B-cells (CD19+) and CTL (CD8+) in NALT. As shown by the cytokine activity testing (IFN-γ, IL-6), the attenuated reassortant virus activates both Th1- and Th2-lymphocytes in NALT.This data suggest that intranasal immunization with live attenuated reassortant viruses (genetic formula 2/6) results into active and balanced stimulation of both Th1-and Th2-immune responses at the primary site of infection (NALT).